Effect of measurement method on an earmuff’s frequency response - Młyński, Rafał; Żera, Jan (Archives of Acoustics, 2007)
Light, medium and heavy earmuffs’ amplitude frequency response was measured using transmission loss technique with a microphone placed in subject’s ear (MIRE – microphone in real ear) and on an artificial test fixture (ATF). Measurements were conducted in frequency range up to 9 kHz employing maximum length sequence (MLS). This method shows details of earmuffs’ amplitude frequency response, in contrast to sound attenuation data obtained in octave bands according to the EN-ISO 4869-1 standard. The study compared ATF data with results measured on a person when soft tissues influenced the ripples of the obtained frequency response. Results were also judged against the sound attenuation data of the real ear at threshold (REAT) method used in certification of hearing protectors.